Evidence update on prevention of surgical site infection. Issue 2 (April 2015) - Leaper, David; Ousey, Karen
<x xml:space="preserve">Abstract</x> Purpose of review Surgical site infection (SSI) is a common healthcare-associated infection and complicates up to 10–20% of operations with considerable strain on healthcare resources. Apart from the widely adopted use of appropriate hair removal, antibiotic prophylaxis, avoidance of hypothermia and perioperative glycaemic control to reduce SSIs, this review has considered new research and systematic reviews, and whether their findings should be included in guidelines. Recent findings The efficacy of preoperative bathing/showering, antibiotic prophylaxis for clean surgery and perioperative oxygen supplementation to reduce the risk of SSI is still in doubt. By contrast, the use of 2% chlorhexidine in alcohol skin preparation, postoperative negative pressure wound therapy and antiseptic surgical dressings do show promise. Antimicrobial sutures in independent meta-analyses were found to reduce the risk of SSI after all classes of surgery (except dirty) whereas the use of wound guards, or diathermy skin incision (compared with scalpel incision), did not. Summary The incidence of SSI after surgery is not falling. Based on this review of published trials and evidence-based systematic reviews some advances might be included into these care bundles. More research is needed together with improved compliance with care bundles.